Numerical investigations on the axial capacity of back-to-back gapped built-up cold-formed stainless steel channels. Issue 10 (July 2019) - Roy, Krishanu; Lau, Hieng Ho; Lim, James BP
Cold-formed stainless steel is becoming popular as a structural member with its increased corrosion resistance and durability when compared with carbon steel. Examples of cold-formed steel structures include trusses, wall frames and portal frames. In cases where increased axial capacity is required, it is becoming increasingly popular to use back-to-back gapped built-up channels, instead of just back-to-back sections. In such an arrangement, however, the beneficial effect of the gap between the back-to-back cold-formed steel channels is ignored by the current design guidelines (American Iron and Steel Institute and the Australian and New Zealand Standard and Eurocode (EN 1993-1-3)) for both cold-formed carbon as well as cold-formed stainless steel. We have considered this issue both experimentally and numerically through finite element analysis for cold-formed carbon steel; from the results of this work, design recommendations were proposed. These results, however, are not applicable to cold-formed stainless steel. This issue is addressed numerically herein. Using the finite element model previously developed for cold-formed carbon steel, an extensive parametric study, comprising 589 models is described. Three different grades of stainless steel, that is, ferritic EN1.4003, austenitic EN1.4404 and duplex EN1.4462 have been considered. The effect of the gap between the two back-to-back channels, slenderness, link-channel spacing and different cross-sectional geometries are investigated. The finite element results were then used to verify the accuracy of current design guidelines by the American Iron and Steel Institute and the Australian and New Zealand Standard and Eurocode (EN 1993-1-3). It was found that the American Iron and Steel Institute and the Australian and New Zealand Standard and Eurocode (EN 1993-1-3) can be over conservative by as much as 68% when calculating the axial capacity of such built-up gapped stainless steel columns. Therefore, a design recommendation is proposed to modify the non-dimensional slenderness so to consider the gap. This leads to the American Iron and Steel Institute and the Australian and New Zealand Standard and Eurocode (EN 1993-1-3) being within 7% conservative to the finite element results.